Komunikasi Risiko Berbasis Masyarakat dalam Menghadapi Banjir di Kabupaten Aceh Barat - Fahrimal, Yuhdi; Husna, Asmaul (Calathu: Jurnal Ilmu Komunikasi, 2023)
Flooding is a hydrometeorological disaster that still poses a threat to people’s lives, especially in rural areas such as Blang Beurandang Village, West Aceh District. Ecological conditions, deforestation, and uncontrolled land use change increase the risk of flooding in an area, in addition to high-intensity rainfall factors. Flood mitigation efforts are not only a structural-technical approach but also require an understanding of community knowledge and experiences that are exchanged in social interactions. Using the concept of community-based risk communication, this research was conducted to explain the risk communication practices carried out by the community of Blang Beurandang Village in dealing with recurrent floods. Data was collected through interviews with ten community informants, who were selected based on predetermined criteria. The results showed that at the community level, risk perception is formed as a subjective assessment of environmental vulnerability, socio-economic vulnerability, hazards, and capacity. Risk perception plays a role in encouraging communities to seek flood risk information from easily accessible sources and use the information channels they have. We recommend a community-based risk communication model that considers the interrelated dimensions of risk perception and risk communication. Keywords: risk communication, risk perception flood, community-based preparedness, environment